Relationship between Risk Management and Microenterprise Sustainability in the Creative Economy Sector - Muhamad Zaenal Asikin; Upit Elya Rohimi (Journal of Sharia Micro Enterprise and Cooperation, 2025)
This study aims to analyze the relationship between risk management and sustainability of micro businesses in the creative economy sector. This study used a quantitative method with an associative approach and cross-sectional design to collect data from 40 micro-enterprise respondents in the creative economy sector in Cirebon. Data were collected through questionnaires and in-depth interviews, and analyzed using multiple linear regression, multicollinearity test, heteroscedasticity, coefficient of determination (R²), and hypothesis testing. The results show that risk management has a significant effect on microenterprise sustainability, with a regression coefficient of 2.00, indicating that improvements in risk management can increase microenterprise sustainability. The t-test and F-test showed strong significance on the risk management variable. The implications of this study provide insights to micro merchants and policy makers on the importance of better risk management implementation, as well as how technology can play a role in risk mitigation. This study also contributes to the development of risk management theory and opens room for further research on the role of digitalization in microenterprise risk management.